Membangun Budaya Kerja yang Unggul melalui Kepemimpinan yang Efektif: Kerangka Konseptual - Dwi Wahyu Artiningsih; Defin Shahrial Putra; Ervica Zamilah; Defin Helda Leliana (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2025)
The focus of this research is to create a conceptual framework that can be used to explain how leaders can promote a better work culture within the company. The main focus of the research is on how leadership styles, organizational culture, and employee motivation relate to each other and how these factors impact performance. Transactional leadership tends to be better at maintaining discipline and structure, but it is less effective in fostering long-term innovation. On the other hand, transformational and servant leadership styles have been proven to enhance employee engagement, motivation, and creativity. To create a positive work environment, there needs to be a supportive work culture, such as open communication, employee empowerment, and recognition of their work. The results show that an inclusive leadership style must be integrated with a strong organizational culture to enhance employee motivation, engagement, and performance. This study contributes to the development of leadership theory and practice in dynamic contemporary organizations.